Telehealth Outpatient Monitoring of a SARS-CoV-2 Familial Cluster Infection in Peru: Adapting to a Healthcare Crisis - Arriola-Montenegro, José (2022)
The coronavirus disease 2019 (COVID-19) epidemic is evolving in Latin America despite implementation of government measures. We report a familial cluster in Lima, Peru, with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Two young and two middle-aged adults with a wide range of COVID-19 manifestations experienced successful management under telehealth outpatient monitoring. Telehealth monitoring was scheduled as suggested by Peruvian Ministry of Health Guidelines and was performed by a designated physician who assessed the patients and prescribed treatment. On May 14, 2020, a 25-year-old male, who worked treating COVID-19 patients, reported constitutional symptoms and tested positive for SARS-CoV-2. Clinical improvement was achieved with azithromycin and ivermectin therapy. He had been in contact with his parents (Cases 2 and 3) and his sister (Case 4). Cases 2 and 3 developed moderate pulmonary compromise requiring oxygen supplementation and pharmacological therapy, including corticosteroids and anticoagulation, under home medical assessment and telehealth monitoring. Case 4 developed mild symptoms and periorbital rash, an atypical dermatological finding. To our knowledge this represents the first report of a familial cluster with COVID-19 that was successfully managed under scheduled telehealth outpatient monitoring in Latin America.